Intrinsically Self-renewing Neuroprogenitors From the A/J Mouse Spiral Ganglion as Virtually Unlimited Source of Mature Auditory Neurons - Rousset, Francis; B. C. Kokje, Vivianne; Sipione, Rebecca; Schmidbauer, Dominik; Nacher-Soler, German; Ilmjärv, Sten; Coelho, Marta; Fink, Stefan; Voruz, François; El Chemaly, Antoun; Marteyn, Antoine; Löwenheim, Hubert; et al. (Frontiers in Cellular Neuroscience, 2020)
Nearly 460 million individuals are affected by sensorineural hearing loss (SNHL), one of the most common human sensory disorders. In mammals, hearing loss is permanent due to the lack of efficient regenerative capacity of the sensory epithelia and spiral ganglion neurons. Sphere-forming progenitor cells can be isolated from the mammalian inner ear and give rise to inner ear specific cell types in vitro. However, the self-renewing capacities of auditory progenitor cells from the sensory and neuronal compartment are limited to few passages, even after adding powerful growth factor cocktails. Here, we provide phenotypical and functional characterization of a new pool of auditory progenitors as sustainable source for sphere-derived auditory neurons. The so-called phoenix auditory neuroprogenitors, isolated from the A/J mouse spiral ganglion, exhibit robust intrinsic self-renewal properties beyond 40 passages. At any passage or freezing-thawing cycle, phoenix spheres can be efficiently differentiated into mature spiral ganglion cells by withdrawing growth factors. The differentiated cells express both neuronal and glial cell phenotypic markers and exhibit similar functional properties as mouse spiral ganglion primary explants and human sphere-derived spiral ganglion cells. In contrast to other rodent models aiming at sustained production of auditory neurons, no genetic transformation of the progenitors is needed. Phoenix spheres therefore represent an interesting starting point to further investigate self-renewal in the mammalian inner ear, which is still far from any clinical application. In the meantime, phoenix spheres already offer an unlimited source of mammalian auditory neurons for high-throughput screens while substantially reducing the numbers of animals needed.